2010
DOI: 10.1080/09672560903552553
|View full text |Cite
|
Sign up to set email alerts
|

The three roles of the ‘Coase theorem’ in Coase's works

Abstract: This article aims at understanding Coase's apparently paradoxical attitude towards his eponym 'theorem'. On the one hand, he judges as excessive the attention devoted to an assertion that makes the assumption of zero transaction costs. On the other, he has never stopped reasserting its largely questioned validity. We explain this puzzle by identifying three roles of the 'Coase theorem' in his works: heuristic (to bring to light the role of transaction costs), critical (of the Pigovian tradition), and normative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Influenced by both the socialist calculation debate and problems such as large-scale industrial pollution, Kapp attempted to move the debate over market 14. See, e.g., Medema 1994Medema , 2009Campbell and Klaes 2005;and Bertrand 2010. failure away from the Pigovian-driven neoclassical framework and into the more broad-based frame of reference often associated with institutionalism. But, as Sebastian Berger shows, Kapp's impact was minimal at best, though the importance of his work was acknowledged by other important scholars such as Buchanan and Guido Calabresi.…”
Section: Market Failures: the Post-world War II Narrowingmentioning
confidence: 99%
“…Influenced by both the socialist calculation debate and problems such as large-scale industrial pollution, Kapp attempted to move the debate over market 14. See, e.g., Medema 1994Medema , 2009Campbell and Klaes 2005;and Bertrand 2010. failure away from the Pigovian-driven neoclassical framework and into the more broad-based frame of reference often associated with institutionalism. But, as Sebastian Berger shows, Kapp's impact was minimal at best, though the importance of his work was acknowledged by other important scholars such as Buchanan and Guido Calabresi.…”
Section: Market Failures: the Post-world War II Narrowingmentioning
confidence: 99%
“…The main object of 'The Problem of Social Cost' was to undermine Pigou's analysis (see, e.g., Bertrand, 2010); hence Coase's insistence on criticism of governmental solutions on one side and his praise of common law judges, who understand the economic problem better than economists do, on the other. But this is not the only element that accounts for this difference of treatment.…”
Section: The Implicit Advantages Of Common Law In Coase's Thoughtmentioning
confidence: 99%
“…Retrospectively, once again, presenting ''The Problem of Social Cost'' in this way may appear reductionist and strangely outdated, viewed the number of recent works about Coase (Bertrand 2006(Bertrand , 2009(Bertrand , 2010McCloskey 1998;Medema 1994Medema , 1995Medema and Samuels 1997;Posner 1993;Klaes 2000) and even by by Coase himself (1994) that have demonstrated that ''The Problem of Social Cost'' is not only a defense of the efficiency of market mechanisms. It has also been stressed that Coase is not a strict, unambiguous defender of market mechanisms.…”
mentioning
confidence: 91%